Non equilibrium Green’s function quantum transport for green multi-quantum well nitride light emitting diodes - Shedbalkar, Akshay; Witzigmann, Bernd (Optical and Quantum Electronics, 2018)
This work presents a non-equilibrium Green’s function (NEGF) based simulation of a green nitride multi-quantum well light emitting diode (LED). A carrier–carrier scattering model based on the Büttiker approach is implemented for LEDs, which has some challenges due to the bipolar nature of the device, large bandgap of nitride devices and non-equilibrium conditions. It is shown that the implemented model, which uses two sets of probe Fermi levels, represents the physics of carrier–carrier scattering in an LED. The simulations provide insight into transport phenomena like tunnelling, hot carriers, back-scattering and accurate DOS in quantized regions. In addition, it is shown that the electron density in the quantum wells is divided into bulk and quantized populations and that the bulk population in the quantum well region does not follow an analytical equilibrium quantum well model.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Büttiker probes; Green LED; NEGF; Two Fermi level method